Ontology-Based Research Asset Management Model for Academic Environment - Modgil, Puneet; Syamala Devi, M. (Journal of Information and Knowledge, 2020)
Data related to research assets are dispersed in various places and heterogeneous formats which may be structured or semi-structured in nature. This scattering of data causes a lot of repetition and inconsistencies. In this paper, we propose an Ontology-Based Research Asset Management Model (ORAM) useful for academic institutions. For this model, we created academic ontology. Data from different academic institutions is mapped to produce a single knowledge base. This mapping is performed by writing mapping rules. This unified knowledge base is integrated with web application to provide a single platform for decision-makers to retrieve information. The ORAM model is tested by developing a prototype with research assets data of various academic institutions available in structured and semi-structured formats. It is concluded that ontology plays a very important role in managing research assets effectively and efficiently.